2005
DOI: 10.1124/jpet.105.090134
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Binding and Functional Antagonism by Xanomeline at the Muscarinic M5Receptor

Abstract: Xanomeline is a functionally selective M 1 /M 4 muscarinic acetylcholine receptor agonist. We have previously identified a novel mode of interaction of this ligand with the muscarinic M 1 receptor that involves persistent binding and activation of the receptor after extensive washout. In the present study, we tested the hypothesis that xanomeline also binds in a washresistant manner to muscarinic receptor subtypes where it exhibits low or no efficacy, such as the M 5 receptor subtype. A secondary hypothesis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
(31 reference statements)
3
20
0
Order By: Relevance
“…In our current study, xanomeline was shown to bind with high-potency at the M3 receptor, similar to that obtained previously at the M1 [18] and M5 receptor [11] using similar expression systems. We have also shown that xanomeline binds to the M3 receptor in a wash-resistant manner similar to other muscarinic receptor subtypes [10, 18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our current study, xanomeline was shown to bind with high-potency at the M3 receptor, similar to that obtained previously at the M1 [18] and M5 receptor [11] using similar expression systems. We have also shown that xanomeline binds to the M3 receptor in a wash-resistant manner similar to other muscarinic receptor subtypes [10, 18].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, its wash-resistant activation of the M1 receptor appears to involve the orthosteric receptor domain. It appears that xanomeline also has unique binding properties at the M2 [10] and M5 [11] receptors. However, it is unclear whether the molecular mechanism of xanomeline binding occurs in a similar manner at all the receptor subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…143 Recent data suggest that xanomeline is also an antagonist at the M 5 receptor. 144 As muscarinic neurons carrying M 5 receptors have synaptic contact with dopaminergic neurons in the brainstem, the functional antagonism of xanomeline at M 5 receptors may offer an additional modulatory pathway on dopaminergic cell-firing.…”
Section: Use Of Cholinesterase Inhibitors In Schizophreniamentioning
confidence: 99%
“…These findings have led to interest in xanomeline as a potential therapy for schizophrenia [12]–[15]. Besides its M 1 /M 4 preference, xanomeline binds to all muscarinic receptor subtypes in a way that is resistant to intensive washing and causes persistent receptor activation or antagonism [16][22].…”
Section: Introductionmentioning
confidence: 99%